Hubungan antara Sikap Orang Tua dan Gerakan Literasi Sekolah dengan Minat Membaca Siswa Sekolah Dasar - Noor, Muhammad; Gamilina, Pranciska (AS-SABIQUN, 2025)
This study is motivated by the limited number of comprehensive quantitative investigations into the simultaneous relationship between parental attitudes and school literacy programs on students' reading interest at the elementary level, despite the fact that low reading interest has significant implications for students' lifelong academic potential and cognitive development. The aim of this study is to analyze the correlation between parental attitudes and school literacy initiatives, both individually and jointly, in relation to students’ reading interest at SDN Simpang Empat 3. A quantitative approach with a correlational design was used, involving 47 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed with bivariate correlation and multiple regression tests. The results show that parental attitude has a significant positive correlation with students’ reading interest (r = 0.462; p = 0.001 < 0.05), as does the school literacy movement (r = 0.422; p = 0.003 < 0.05). Simultaneously, both variables significantly contribute to students’ reading interest (R² = 0.349; p = 0.000 < 0.05), indicating that these two factors together explain 34.9% of the variation in reading interest, with the remaining influence attributed to other factors beyond the scope of this study. The main conclusion of this research is the importance of synergy between positive parental attitudes and effective implementation of school literacy programs in fostering students’ reading interest. The implications include the need to strengthen home-school collaboration and optimize literacy initiatives to support the development of a reading culture from an early age. This study also recommends further research to explore causal relationships and extend the generalizability of the findings across diverse educational contexts.